Changes in macular pigment optical density and serum concentrations of its constituent carotenoids following supplemental lutein and zeaxanthin: The LUNA study - Trieschmann, Meike; Beatty, Stephen; Nolan, John M.; Hense, Hans Werner; Heimes, Britta; Austermann, Ulrike; Fobker, Manfred; Pauleikhoff, Daniel (Experimental eye research, 2007)
Macular pigment (MP), consisting of lutein (L) and zeaxanthin (Z), is believed to protect the retina from photo-oxidative damage. The current study investigates, in terms of MP optical density (MPOD) and serum concentrations of its constituent carotenoids, response to supplemental L and Z, and co-antioxidants. An intervention (I) group, consisting of 108 subjects (mean [±SD] age: 71.5 [±7.1] years), of which 92.6% exhibited features of age-related macular degeneration (AMD), received a daily supplement consisting of 12 mg L and 1 mg Z, both provided as ester 120 mg vitamin C, 17.6 mg vitamin E, 10 mg zinc, 40 μg selenium (Ocuvite Lutein™) for a period of 6 months. MPOD was measured, by 2-wavelength autofluorescence (AF), on five occasions during the period of supplementation, and once again 3 months following discontinuation of the supplement. A control (C) group of 28 subjects (mean [±SD] age: 71.0 [±8.1] years), who received no dietary supplementation or modification, was examined at baseline and once again after a mean of 29.4 (±9.3) weeks. At baseline, mean (±SD) MPOD (at 0.5°) was 0.504 (±0.197) and 0.525 (±0.189) in the I and C groups, respectively. There was a statistically significant increase in MPOD (at 0.5°) for the I group (0.1 [±0.009]; p < 0.0008), whereas no significant increase was seen in the C group (0.03 [±0.02]; p > 0.05), over the period of supplementation. In order to classify supplemented subjects into quartiles, in terms of MPOD response, we calculated the difference between MPOD (at 0.5°) at visit 6 and at baseline (visit 1). Quartile 1 (the “non-responder” quartile) displayed no increase in MPOD (at 0.5°), in spite of rises seen in serum concentrations of L and Z. The three “responder” quartiles reached similar final plateaus of MPOD (at 0.5°), reflected in final mean (±SEM) values of 0.59 (±0.04) optical density unit (ODU), 0.64 (±0.03) ODU and 0.64 (±0.03) ODU for quartiles 2, 3 and 4, respectively. Subjects with low baseline MPOD were more likely to exhibit a dramatic rise in MPOD, or to exhibit no rise in MPOD, in response to supplements than subjects with medium to high baseline MPOD values. Supplementation with 12 mg L and 1 mg Z, combined with co-antioxidants, resulted in an increase of MPOD at 0.5° eccentricity in a majority of subjects, including those afflicted with AMD. However, there remains a substantial proportion of subjects for whom, in spite of rises in serum concentrations of L and Z in these subjects, MPOD augmentation in response to supplemental L, Z and co-antioxidants could not be detected over the study period, thus indicating that intestinal malabsorption of these carotenoids is not responsible for the lack of a macular response to such supplements. Further, our results suggest that saturable mechanisms play a role in the retinal capture and/or stabilisation of the macular carotenoids.